LEGO architecture the visual guide - Wilkinson, Philip 1955-; Tucker, Adam Reed (New York, New York DK Publishing, 2014)
"Iconic buildings reimagined in LEGO bricks"--Container.
Stunning images and in depth exploration of the real buildings like the Guggenheim or the Empire State Building, on which the LEGO Architecture series is based, provide you with a comprehensive look at the creation of these intricate sets. Learn why the LEGO team chose certain pieces and what particular challenges they faced. Read about the inspiration behind the creative processes and what designing and building techniques were used on various sets. Featuring profiles of the LEGO artists and builders who created the series.
Timeline -- LEGO® artist profiles -- The creative process -- Fallingwater® in development -- Glossary -- LEGO cityscape in scale -- Solomon R. Guggenheim Museum® -- Fallingwater -- The White House -- Farnsworth House -- Rockefeller Center -- Robie House -- Brandenburg Gate -- Sydney Opera House -- Big Ben -- Villa Savoye -- Sungnyemun -- The Leaning Tower of Pisa -- Imperial Hotel -- United Nations Headquarters -- The Eiffel Tower -- Trevi Fountain -- John Hancock Center -- Willis Tower -- Empire State Building -- Seattle Space Needle -- Burj Khalifa -- Marina Bay Sand
Includes index.
Keywords: LEGO to; Architectural mode